(untitled) (International Journal of Physiotherapy, 2015)
Background: Musculoskeletal disorders are widespread in many countries around the world. It has been reported that about 58 percent of the world’s population over the age of 10 years spent one third of their life span at work. The population at a high risk include nursing facilities, transportation, mining, food processing, leather tanning, heavy and light manufacturing. Transport workers have been found to be at high risk of developing work related musculoskeletal disorders (WRMSDs). There has been literature evidence regarding the prevalence of musculoskeletal disorders in bus drivers of various cities of different countries. But no study has been done so far in Tricity (Chandigarh, Panchkula and Mohali) for the same. The purpose of this study is to investigate the prevalence and characteristics of work related musculoskeletal disorders (WRMSDs) among bus drivers of Tricity. Methods: 300 bus drivers were included in the study according to the inclusion and exclusion criteria. The standardized Nordic questionnaire for musculoskeletal disorder and a self administered questionnaire were filled by therapist after the personal interview of each driver. Results: Unpaired t test was used to measure the difference in variable of two groups and Karl Pearson’s correlation coefficient was used to determine the correlation between two entities. In the present study, the subjects were in the age group of 25 to 50 years. Out of the total sample of 300 male bus drivers in Tricity, 159 reported that they had WRMSDs. The prevalence of WRMSDs among bus drivers in Tricity was 53%. In present study, the prevalence of low back pain was highest among the bus drivers that are 30.3%, then neck pain 17.3%, knee pain 14.7%, shoulder 6.3%, ankle and feet 5.7%, upper back 4%, hip and thigh 4%, elbow 1.3% and wrist and hand 1.3%. Thus low back pain, neck pain and knee pain are the most prevalent WRMSDs amongst bus drivers. Conclusions: Work-related biomechanical considerations have been found to form important health risk factors for musculoskeletal disorders among bus drivers. The prevalence of work-related musculoskeletal disorders among the bus drivers in Tricity is found to be as high as 53%. It is also concluded that the low back (30.3) and neck (17.3) are the most common sites susceptible to injury followed by knees (14.7%) shoulder (6.3%), and ankle/feet (5.7%). Therefore present study results strongly indicate the need for education programmes on ergonomic advice and other precautions for prevention of musculoskeletal disorders in bus drivers should be made mandatory in order to decrease the risk of WRMSDs which may help in improving their quality of life.